sFlt-1 Levels as an Indicator of the Effectiveness of Antihypertensive Agents in Gestational Hypertension - Riska Khoirfatud Rahmawati; Yulistiani; Ernawati; Marcha Debby S; Dian Ika Rahmawati (International Journal of Health and Pharmaceutical (IJHP), 2026)
Gestational hypertension is reported to increase maternal morbidity and mortality, linked to higher levels of soluble fms-like tyrosine kinase-1 (sFlt-1) that lead to endothelial dysfunction. Methyldopa and nifedipine are thought to improve the angiogenic profile, but there are limited data on the effect on the sFlt-1 levels. Therefore, this study aimed to evaluate how methyldopa alone and the combination of methyldopa with nifedipine affect sFlt-1 levels and mean arterial pressure (MAP) in cases of gestational hypertension. This prospective observational study included 30 patients with gestational hypertension who were divided into the methyldopa monotherapy (n=15) and methyldopa-nifedipine combination group (n=15). sFlt-1 levels were calculated utilizing the enzyme-linked immunosorbent assay (ELISA) method in the first 24 hours of hospitalization (prepartum) and 24 hours after delivery (postpartum). The results showed that the combination group experienced a decrease in sFlt-1 levels and MAP by 23.8% (p<0.05) and 13.1% (p<0.001), respectively. These values were greater than those of the monotherapy group, which only reduced sFlt-1 levels by 18.8% (p>0.05) and MAP by 10.4% (p<0.05). A more consistent decrease in sFlt-1 levels was observed in five patients with severe preeclampsia who received additional magnesium sulphate (MgSO₄). In conclusion, methyldopa monotherapy and the combination of methyldopa-nifedipine reduced sFlt-1 and MAP levels. This result made sFlt-1 levels a marker of the effectiveness of antihypertensive therapy in gestational hypertension.